(untitled) (Research, Society and Development, 2021)
The genetic material adapted to the Cerrado Mineiro conditions and the monitoring can be a determining factor for the efficient management of coffee pests and diseases. In this context, the objective was to evaluate the climatic conditions in the cercosporiosis incidence and leaf-miner in coffee cultivars in Monte Carmelo, Minas Gerais. The experiment was conducted at the Federal University of Uberlandia, Campus Monte Carmelo. The experimental design used was in randomized blocks, with four blocks, and the treatments consisted of eight cultivars of Coffea arabica L.: Acaiá Cerrado MG-1474; Mundo Novo IAC 379-19; Bourbon Amarelo IAC J10; Catuaí Vermelho IAC 99; Paraíso MG H 419-1; Topázio MG-1190; Acauã Novo and IAC 125 RN. Each experimental plot consisted of 10 plants, with the five central plants being evaluated. The presence of cercosporiosis lesions in the branch located in the upper third was evaluated monthly by the non-destructive method. Fortnightly the number of leaves with intact mines of the leaf-miner in the plagiotropic branch selected in the middle third was counted. The incidence of cercosporiosis and leaf-miner was evaluated from December 2017 to August 2018. The cultivars that presented the lowest incidence of leaf-miner were Mundo Novo IAC 379-19, Acaiá Cerrado MG-1474, Bourbon Amarelo IAC J10, Paraíso MG H 419-1 and Topázio MG-1190, respectively. The highest incidence of leaf-miner was from April to August. The months with the highest incidence of cercosporiosis were from December to May, with variability in the occurrence of the disease among the cultivars tested.